2018
DOI: 10.2478/acph-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes α-humulene and β-caryophyllene oxide enhance the efficacy of 5-fluorouracil and oxaliplatin in colon cancer cells

Abstract: The present study is designed to find out if sesquiterpenes, α-humulene (HUM), valencene (VAL), β-caryphyllene-oxide (CAO) and trans-nerolidol (NER), are able to improve the antiproliferative effect of classical cytostatic drugs, 5-fluorouracil (FU) and oxaliplatin (1,2-diaminocyclohexaneoxalato-platinum, OxPt), in colon cancer cell lines Caco-2 and SW-620. In addition, the possible mechanisms of sesquiterpene action are studied. The results show significant ability of HUM and especially of CAO to enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…The doxorubicin chemosensitization by β-caryophyllene in cholangiocarcinoma cells is in agreement with our previous evidence in HepG2 [26]. Similarly, β-caryophyllene oxide produced synergistic effects towards doxorubicin and other anticancer drugs in liver, breast, leukemic and colon cancer cells [24][25][26][72][73][74]. Interestingly, doxorubicin-chemosensitization by β-caryophyllene occurred after both a long-term exposure of 24 h and under the metronomic schedules, like in HepG2 cells [26].…”
Section: Discussionsupporting
confidence: 89%
“…The doxorubicin chemosensitization by β-caryophyllene in cholangiocarcinoma cells is in agreement with our previous evidence in HepG2 [26]. Similarly, β-caryophyllene oxide produced synergistic effects towards doxorubicin and other anticancer drugs in liver, breast, leukemic and colon cancer cells [24][25][26][72][73][74]. Interestingly, doxorubicin-chemosensitization by β-caryophyllene occurred after both a long-term exposure of 24 h and under the metronomic schedules, like in HepG2 cells [26].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, both sesquiterpenes have been highlighted to possess interesting chemopreventing properties, due to their ability to counteract cell injury induced by environmental pollutants [49][50][51][52] and to inhibit cancer cell growth and proliferation, through affecting several key pathways for cancer development, such as mitogen-activated protein kinase (MAPK), PI3K/AKT/mTOR/S6K1 and STAT3 pathways [47,[53][54][55][56]. Also, they were reported to potentiate the efficacy of some anticancer drugs, acting as chemosensitizers [15][16][17]19,20].…”
Section: Discussionmentioning
confidence: 99%
“…For evaluating the chemosensitizing properties, the anticancer drug and the chemosensitizing agents were administered to cells according to the co-treatment protocol. Two non-cytotoxic concentrations of the sesquiterpenes (about IC 10 and IC 20 concentrations, at which a 10% and 20% cytotoxicity was produced) were tested. Progressive concentrations of the anticancer drug were prepared in sterile tubes and gently mixed with the test substances or the vehicle.…”
Section: Combination Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…antioxidant, antibacterial, antiparasitic and anticancer). Recently, it has been also shown that CAO enhances the efficacy of 5-fluorouracil and oxaliplatin in colon cancer cells (Ambrož et al 2019).…”
Section: Introductionmentioning
confidence: 99%